ANALISIS DAMPAK NEGATIF YANG DITIMBULKAN PEDAGANG KAKI LIMA TERHADAP PENGEMBANGAN TATA RUANG KOTA TIMIKA KABUPATEN MIMIKA - Habel Taime (JURNAL KRITIS (Kebijakan, Riset, dan Inovasi), 2021)
This study aims to determine the negative impact caused by street vendors on the spatial planning of the city of Timika, Mimika Regency. The method used is a descriptive method with a qualitative approach. The results of the analysis show that the violations in question are violations of road order as many as 1,759 cases and violations of green lane order as many as 141 cases. The number of cases of this violation is only counted as street vendors who live on the edge of arterial roads and green belt areas, not including street vendors who move around, and who practice on certain days or at certain hours. When viewed from the hours of operation, there are still a lot of street vendors who carry out special activities at night such as night stalls which generally occupy locations right on the edge of the highway. They operate only at night and sometimes always move from place to place. This condition shows that the presence of street vendors in the city of Timika, both permanent and moving places, also has a negative influence on the spatial development of Timika, Mimika Regency. The results of this study prove that the research hypothesis can be accepted, namely the presence of street vendors has a negative influence on the spatial development of Timika City, Mimika Regency.